Handing over patients from the ICU to the general ward: A focused ethnographical study of nurses' communication practice. (14th August 2017) - Bunkenborg, Gitte; Bitsch Hansen, Tina; Hølge‐Hazelton, Bibi
Abstract: Aim: To explore nursing practice and perception of engaging in communicative interaction when handing over multi‐morbid patients from the ICU to general medical or surgical wards. Background: Communication failures impose risks to patient safety. ICU and general ward nurses communicate in writing and verbally when handing over patients from one setting to another. A deeper understanding of nurses' communicative interaction and of nurses' perception of their interaction is crucial to facilitate clinical interventions focusing to improve patient safety. Design: An explorative, qualitative design using focused ethnography was applied to the study. Methods: Participant observation of 22 clinical situations of handing over patients from the ICU to general wards was conducted in November and December 2015, followed by five focus group interviews, three interviews with general ward nurses and two with ICU nurses in January–February 2016. Observation notes and interview transcripts were analysed using content analysis. Findings: The theme "Communicative interaction as a process of sharing and adopting ownership" and the subtheme "Communicative interaction influenced by nurses individual expectations towards patient status and the handing over process" emerged from observation notes. From transcribed focus group interviews, the theme "Balancing and negotiating when passing on, consuming and adapting knowledge" was identified. Conclusion: A lack of shared goals regarding handing over patients from a high monitoring unit to general wards causes communicative and collaborative difficulties, loss of information and potential risks to patients. Organizational attention in relation to ICU discharge is crucial to improve collaboration, communication and patient safety.